Preparation of ultrafine Ti powder by inhibitor coated/HDH combined method. (1st July 2013) - He, W; Weng, Q G; He, Y H; Jiang, Y
Abstract : Ultrafine Ti powder was prepared by hydrogenation of titanium sponge, mechanical pulverisation, inhibitor coating, vacuum dehydrogenation and inhibitor removal. The effects of technological parameters on Ti powder morphology, particle sizes and oxygen content were investigated. The results showed that after hydrogenation at 700°C for 2 h and mechanical pulverisation for 5 h, the titanium hydride powder with D 50 of 2·61 μm was obtained. Then the ultrafine titanium powder with oxygen content of 0·89 wt-%, D 50 of 6·16 μm and irregular morphology was obtained by procedures of coating titanium hydride powder with NaCl, dehydrogenising at 630°C for 2 h and removing NaCl. The addition of NaCl resulted in a negligibly increase in the oxygen content in Ti powder. The Ti particles growth during dehydrogenation was effectively inhibited by the coated NaCl on Ti particles with thickness of 5-10 nm as an isolation layer to block atomic diffusion.